The heterogeneity of FDI in Sub-Saharan Africa: How do the horizontal productivity effects of emerging investors differ from those of traditional players? - Birte Pfeiffer; Holger Görg; Lucia Perez-Villar (Kiel Institute for the World Economy (IfW), 2015)
This paper analyzes the horizontal productivity effects of foreign direct investment (FDI) from industrialized and developing countries in 10 sub-Saharan African countries. We establish a unique data set by combining data from the World Bank Enterprise Surveys that allow us to distinguish between foreign investors from sub-Saharan Africa, Asia, Europe, the Middle East, and North Africa. We find strong evidence of horizontal productivity spillovers to domestic firms derived from foreign-firm presence. However, these effects are clearly dependent on domestic firms' absorptive capacity. The largest productivity effects seem to be driven by investors from sub-Saharan Africa. Our analysis also shows that productivity effects differ according to the income level of host countries. Overall, the strongest productivity effects seem to materialize in lower-middle-income countries. These key findings emphasize the increasing importance of emerging investors, beyond the traditional players from industrialized countries, in sub-Saharan Africa.
Keywords: F23; 330; foreign direct investment; productivity; South-South firms; spillovers; sub-Saharan Africa